Percutaneous hook wire assistance during laparoscopic excision of an intrarenal mass - Kouriefs, C (Ann R Coll Surg Engl, 2019)
Completely endophytic renal tumours pose challenges in laparoscopic nephron-sparing tumour excisions, with the use of intraoperative imaging techniques (e.g. ultrasound) being crucial when managing such tumours. The use of a percutaneous hookwire for tumour localisations are in use in several other surgical fields, such as breast surgery. An asymptomatic 52-year-old man presented with an incidental small right sided solid 33-mm interpolar renal mass identified on computed tomography. A guided insertion of a percutaneous localisation wire was carried out prior to a laparoscopic partial nephrectomy to assist in intraoperative tumour landmark/margins identification. Operative time was 210 minutes with zero ischaemia time, with an estimated blood loss of 200 ml. No perioperative complications were observed and the patient was discharged two days postoperatively. Histology revealed the mass to be a Fuhrman grade 2 clear-cell carcinoma with a 2-mm clear surgical margin. The patient remained free of recurrence at 16 months of follow-up. We have reported our first experience of wire localisation prior to laparoscopic partial nephrectomy for an intrarenal mass, which to our knowledge could be the first of its kind in renal surgery. Percutaneous wire localisation of endophytic renal tumours is potentially safe and effective and can allow nephron-sparing surgery where laparoscopic ultrasound is not available. Longer-term and further evidence should be encouraged.